Transient riboflavin depletion in preterm infants. Issue 9 (September 1984) - Lucas, A; Bates, C
Abstract : Biochemical riboflavin status was measured in 68 preterm infants who were receiving either human milk or a preterm infant formula (containing riboflavin, 1.8 mg/l) during the first few weeks of life. The relation between riboflavin status, type of diet, and time of introduction of a multivitamin supplement containing riboflavin was analysed and the duration of phototherapy was recorded. Those who received the multivitamin supplement on or before day 7 of life seldom became deficient and no significant difference between diets was seen in this group. Of those who received the supplement after day 7, human milk fed infants commonly developed abnormal riboflavin status (18 out of 23 infants) compared with a small and significantly lower incidence in the formula fed group. Dietary effects on riboflavin status seemed to outweigh in importance those of phototherapy. It is concluded that the riboflavin content of human milk, which may be lowered by photodegradation, is not sufficient to ensure normal biochemical status in preterm infants. The larger amounts provided by a multivitamin supplement or by a preterm infant formula may, however, prevent biochemical deficiency. The desirability (and safety) of routine riboflavin supplementation of preterm infants is discussed.